Factors Affecting the Performance of Clinical Nurses - Ullah, Tariq; Ullah, Rafi; Khan, Asad; Khan, Jehan Zaib; Jan, Syed Shahabudin (International Journal of Social Sciences and Management, 2018)
The purpose of the research was to explore the factors that affect the performance of nurses in Nawaz Sharif Social Security Hospital Lahore. The Research Design was quantitative descriptive. The population consisted of all categories of nurses working Nawaz Sharif Social Security Hospital Lahore works seven days in a week. The Stratified Random sampling technique was used to obtain the sample. Data were collected by means of designed performance instrument questionnaires. The study revealed that nurses were dissatisfied with their work, something that had a tremendous influence on their performance. Int. J. Soc. Sc. Manage. Vol. 5, Issue-3: 125-137